2009
DOI: 10.1038/hr.2009.27
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome of hypertension-induced left ventricular hypertrophy and its regression by antihypertensive therapies

Abstract: Left ventricular hypertrophy (LVH), a common consequence of systemic hypertension associated with poor clinical outcome, is also a potentially reversible condition. Here, we probed the molecular pathways that underpin the development of LVH and their modulation by antihypertensive regimens that reversed LVH. Spontaneously hypertensive rats were studied at 12 (early LVH) and 48 weeks (late LVH), respectively, with normotensive Wistar-Kyoto rats as age-matched controls. Three treatment groups were maintained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
1
8
1
Order By: Relevance
“…In this regard, several key regulators of muscle cell growth and proliferation (MAP3K7IP2, MSTN, PHB2, APOBEC3F) and gene expression (PTPLAD1, JMJD1C, CEP290) are differentially expressed between LV and RV piglet myocardium that may be relevant to intrinsic differences [31] that can regulate the chamber-dependent response of ventricular myocardium to workload. Interestingly, transition from “early” to “late” hypertension-induced hypertrophy in young adult rats is associated with predominant changes in expression of cell growth/proliferation and signal transduction factors [32]. …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several key regulators of muscle cell growth and proliferation (MAP3K7IP2, MSTN, PHB2, APOBEC3F) and gene expression (PTPLAD1, JMJD1C, CEP290) are differentially expressed between LV and RV piglet myocardium that may be relevant to intrinsic differences [31] that can regulate the chamber-dependent response of ventricular myocardium to workload. Interestingly, transition from “early” to “late” hypertension-induced hypertrophy in young adult rats is associated with predominant changes in expression of cell growth/proliferation and signal transduction factors [32]. …”
Section: Discussionmentioning
confidence: 99%
“…9, 19 Our data confirmed that all patients’ RV functional parameters improved after LT. Of note, RV hypertrophy was also resolved in all patients, in which mechanism can be seen in the reversibility of LV hypertrophy in hypertensive patients under antihypertensive therapies. 20, 21 Meanwhile, pre-existing LV dysfunction is a primary determinant for eliminating LT candidacy at many centers. 9, 19 In our cohort, all patients had a preserved LV function before LT (mean LVEF 58.9±6.0%), which did not change after LT (57.9±9.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest was the analysis of unique transcripts arising from novel exons, splice variants and alternate sites of initiation/termination otherwise absent from mainstream genome databases . The transcriptome of left ventricular hypertrophy has been investigated, observing close to 300 transcripts altered during early stages of disease progression . This study also investigated the modulation of the transcriptome in response to pharmacological intervention and observed that whilst the disease showed regression, there was an absence of significant changes , indicating a level of control beyond the transcriptome.…”
Section: Cvd and The Genomementioning
confidence: 99%
“…The transcriptome of left ventricular hypertrophy has been investigated, observing close to 300 transcripts altered during early stages of disease progression . This study also investigated the modulation of the transcriptome in response to pharmacological intervention and observed that whilst the disease showed regression, there was an absence of significant changes , indicating a level of control beyond the transcriptome. As discussed above, if poor adaptation to changing conditions is the prelude to disease, proteins, as mediators of cellular function, also play an integral role in the cellular phenotype.…”
Section: Cvd and The Genomementioning
confidence: 99%